Synthetic glycoscapes: addressing the structural and functional complexity of the glycocalyx. Issue 2 (6th April 2019) - Purcell, Sean C.; Godula, Kamil
Abstract : The glycocalyx is an information-dense network of biomacromolecules extensively modified through glycosylation that populates the cellular boundary. The glycocalyx regulates biological events ranging from cellular protection and adhesion to signalling and differentiation. Owing to the characteristically weak interactions between individual glycans and their protein binding partners, multivalency of glycan presentation is required for the high-avidity interactions needed to trigger cellular responses. As such, biological recognition at the glycocalyx interface is determined by both the structure of glycans that are present as well as their spatial distribution. While genetic and biochemical approaches have proven powerful in controlling glycan composition, modulating the three-dimensional complexity of the cell-surface 'glycoscape' at the sub-micrometre scale remains a considerable challenge in the field. This focused review highlights recent advances in glycocalyx engineering using synthetic nanoscale glycomaterials, which allows for controlled de novo assembly of complexity with precision not accessible with traditional molecular biology tools. We discuss several exciting new studies in the field that demonstrate the power of precision glycocalyx editing in living cells in revealing and controlling the complex mechanisms by which the glycocalyx regulates biological processes.